ANALYZING STUDENTS' PERCEPTION ON THE USE OF ARTIFICIAL INTELLIGENCE (AI) IN WRITING ENGLISH ESSAYS AT ISLAMIC UNIVERSITY OF INDRAGIRI - Nisva Okta Selly; Samsul Amri; Sri Erma Purwanti (J-Shelves of Indragiri (JSI), 2025)
The importance of conducting this research is to determine whether AI can be a possible tool for students to assist them in writing English essays. There is a gap between the theoretical potential of AI tools in improving English essay writing and the practical challenges faced by students, such as the issue of plagiarism, inaccurate information, and unstable internet access in using AI when writing English essays. This study aims to identify students’ perception on the use of Artificial Intelligence (AI) in writing English essays at Islamic University of Indragiri. The method used in this study is a quantitative descriptive approach with data collection techniques through a questionnaire consisting of 25 statement items, which were given to 64 students. Data were analyzed using a 4-point Likert scale. The results showed that the majority of students had a positive perception of their familiarity and understanding of AI, as well as its benefits in writing English essays. However, their perceptions of the originality and accuracy of the information provided by AI tended to be neutral, considering that some of the information obtained was not always in accordance with the topic or was inaccurate. On the other hand, obstacles such as unstable internet connection quality also affected the effectiveness of using AI. Overall, students' perceptions of the use of AI in writing English essays can be categorized as moderate, with differences of opinion regarding its advantages and limitations.